Quality of Software Costs Money--Heartbleed Was Free. - KAMP, POUL-HENNING (Communications of the ACM, 2014)
The article focuses on ways to raise funding for free and open source software (FOSS). Topics discussed include improving the quality of FOSS by ensuring that developers are funded properly, a call for companies to add FOSS support to their corporate social responsibilities, and software projects' establishment of foundations to raise money and hire developers. Also mentioned are the author's experience with crowdfunding, the benefits of having fewer but larger sponsors rather than individual sponsors, and the features of the Varnish Moral License (VML) funding model.